Coccidioidomycosis with diffuse miliary pneumonia - Sotello, David (Proc (Bayl Univ Med Cent), 2016)
Coccidioidomycosis is a well-known infection in the southwestern United States, and its occurrence is becoming more frequent in endemic areas. This disease can have a significant economic and medical impact; therefore, accurate diagnosis is crucial. In conjunction with patient symptoms, residence in or travel to an endemic area is essential for diagnosis. Diagnosis is usually made with serology, culture, or biopsy and confirmed with DNA probe technology. Pulmonary disease is the most common presentation and is seen in almost 95% of all cases. One-half to two-thirds of all Coccidioides infections are asymptomatic or subclinical. Most pulmonary infections are self-limited and do not require treatment except in special populations. When treatment is warranted, itraconazole and fluconazole are frequently used. Diffuse miliary pneumonia is uncommon and is especially rare in immunocompetent patients. Herein we describe a rare presentation of miliary coccidioidomycosis in a nonimmunocompromised patient.